CORRELATION BETWEEN CONDENSED TANNIN AND FIBER CONTENT OF IRRADIATED POMEGRANATE SEED - Zarei, Mohsen; Shawrang, Parvin (Journal of Agricultural Sciences (Belgrade), 2016)
Electron beam and gamma ray irradiation exposed to pomegranate seed at doses of 5, 10, 15 and 20 kGy to study the relationships between their condensed tannin, NDF, ADF content, in vitro rumen methane production and protozoa population. Data were analyzed by using the GLM procedure. Orthogonal contrast showed that gamma irradiation significantly increased NDF content of pomegranate seed as compared to control, however electron beam irradiation did not significantly affect NDF%. Condensed tannin content of pomegranate seed was significantly decrease by gamma and electron beam irradiation compared to control. Our results showed that there was a negative correlation between methane production and NDF content of gamma irradiated pomegranate seed. This means that the methane production of gamma irradiated pomegranate seed decreased with increasing NDF%. Therefor it seems that in addition to tannin, the reduction of CH4 production was affected by cell wall content. Generally, cell wall contents may be more important than tannins in limiting microbial and in vitro fermentation.